120P Combination of triptorelin with nivolumab in ICI resistant advanced melanoma. (15th December 2019) - Robert, C; Lejeune, F J; Lebbé, C; Lesimple, T; Lundström, E; Nicolas, V; Gavillet, B; Grégoire, V; Crompton, P
Abstract: Background: It has been shown that androgens are immunosuppressive. Androgen deprivation with GnRH agonists regenerates the thymus and its functions in adults, leading to increase in blood and lymphoid organ lymphocytes, in naive lymphocytes with expansion of TCR Vbeta repertoire, and in Tumour Infiltrating Lymphocytes (TILs) in prostate tumours. This phase I study evaluated the safety of triptorelin in combination with nivolumab, as well as its potential to reverse resistance to PD-1 inhibitors in male melanoma patients. Methods: Treatment consisted of triptorelin 3.75 mg i.m. every 4 weeks and nivolumab 3 mg/kg i.v. every 2 weeks. Bicalutamide 50 mg p.o. QD was added for the first 28 days. Evaluation of response was performed after 3 months. Triptorelin PK was assessed and various PDy markers were measured in blood and tumour samples. Planned treatment duration was 48 weeks. Results: Fourteen male patients were included, of whom 11 were white and 3 were black, with mean age 65 years (range 45-82). At screening 4 were locally advanced while 10 had distant metastases (2 with M1a, 1 with M1b, 6 with M1c and 1 with M1d). Ten patients had cutaneous melanoma, 2 patients had mucosal melanoma, and 2 had an unknown primary. Safety: No grade 4 AEs were reported. Five grade 3 AEs were reported in 4 patients, of which one (abdominal pain) was attributed to triptorelin and resolved after 39 days (causing no treatment interruption as it started on the day treatment was discontinued due to progression), and one (neutropenia) was considered related to nivolumab and resolved following treatment interruption for 14 days. Efficacy: BOR (RECIST 1.1) was assessed as 2 PR, 5 SD, and 7 PD. The two patients with PR showed reductions from baseline in Target Lesions of 76% (one pancreas metastasis) and32% (two inguinal lymph nodes), following an initial pseudoprogression. Conclusion: The association of triptorelin to nivolumab was well tolerated and yielded partial response in two patients. Legal entity responsible for the study: Debiopharm International S.A. Funding: Debiopharm International S.A. Disclosure: C. Robert: Advisory / Consultancy: Novartis, Bristol-Myers Squibb, MSD, Roche, Sanofi, Amgen, Pierre Fabre. F.J. Lejeune: Honoraria (self): Debiopharm International SA. C. Lebbé: Honoraria (self): Roche, Bristol-Myers Squibb, Novartis, MSD, Amgen, Pierre Fabre, Pfizer, Incyte; Advisory / Consultancy: Roche, Bristol-Myers Squibb, Novartis, MSD, Amgen; Travel / Accommodation / Expenses: Bristol-Myers Squibb, MSD; Speaker Bureau / Expert testimony: Roche, Bristol-Myers Squibb, Novartis, Amgen; Advisory / Consultancy: Aventis. T. Lesimple: Research grant / Funding (self): Roche; Advisory / Consultancy: MSD, Novartis, Pierre Fabre. E. Lundström: Full / Part-time employment: Debiopharm International SA. V. Nicolas: Full / Part-time employment: Debiopharm International SA. B. Gavillet: Full / Part-time employment: Debiopharm International SA. V. Grégoire: Full / Part-time employment: Debiopharm International SA. P. Crompton: Full / Part-time employment: Debiopharm International SA.